Berian sebagai Nafkah kepada Calon Isteri Perspektif Mazhab Syafi’i (Studi Kasus di Tenom, Sabah Malaysia) - Morti, Mohamad Farid Adam Bin; Fatimah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study examines the practice of giving gifts or pulut by prospective husbands to prospective wives during the engagement period among the Muslim community in Tenom, Sabah, Malaysia. This practice has become deeply rooted as part of a social tradition that is considered an unwritten obligation, whereby the male party gives a certain amount of money every month from the time the proposal is accepted until the wedding day arrives. The amount varies according to family agreement, ranging from RM 300 to RM 1,000 per month, with the duration of the gift ranging from seven months to over a year. This phenomenon raises questions about the legal status of the down payment in the context of Islamic law, as well as its social impact on the prospective bride and groom. This study uses an empirical legal method with a field research approach. Primary data was obtained through in-depth interviews and direct observation of prospective grooms, prospective brides, families, traditional leaders, and religious leaders. Secondary data was collected from Islamic legal literature, Malaysian legislation, and related academic sources. Data analysis was conducted qualitatively by grouping findings based on main themes, namely the form of implementation, public perception, and Islamic legal views on the practice. The results of the study show that the public considers the down payment as a symbol of the prospective husband's seriousness and moral responsibility, but this practice can become a heavy financial burden, leading to marriage cancellations or elopements. In Islamic law, gifts given during the engagement period do not fall under the categories of dowry or maintenance, but are more appropriately categorized as gifts or customary practices permitted as long as they do not contradict Islamic law. The research discussion emphasizes the need for community education to ensure that this custom is carried out voluntarily and proportionally, so as not to hinder the purpose of marriage that is pleasing to Allah SWT.